Cool planning: How urban planning can mainstream responses to climate change - Newman, Peter (ELSEVIER SCI LTD, 2020)
Climate change action requires both adaptation and mitigation. Both need urban planning in strategic and statutory processes to mainstream the innovations now appearing. Integrating adaptation and mitigation is demonstrated using two planning tools: water sensitive urban design and biophilic urbanism and both need to be mainstreamed through urban planning in a rapidly warming world. Mitigation must be about grasping the need for decoupling fossil fuel use from GDP and data indicates this is underway. Cities like Shanghai and Beijing are showing how emerging cities can decouple wealth and car use. Disruptive innovations underway are solar and wind power, batteries, and electrifying transport but need planning tools to mainstream them. Emerging disruptive innovations include Trackless Trams that function like light rail but at significantly less cost and Hydrogen in fuel-cell vehicles for heavy transport and as an industrial fuel. The Theory of Urban Fabrics is used to show how emerging innovations can be mainstreamed in urban planning through each of the different fabrics of the city. This is illustrated using the six tools outlined in this paper to demonstrate how such nuanced and integrated urban planning responses to climate change can be mainstreamed.